Behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions through a celluose fiber supported solid membrane - Gaikwad, Abaji G. (Macedonian Journal of Chemistry and Chemical Engineering, 2012)
A newly designed membrane cell was used to study the behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions using a cellulose fiber supported solid membrane. The cellulose fiber membrane was prepared by the chemical modification of cellulose fiber using an esterification reaction with citric acid. Different experimental variables were investigated, such as time, membrane size, stirring of the source and receiving phases and the pH of the source phase. The use of different stripping agents in the receiving phase was explored, including nitric acid, hydrochloric acid, sodium nitrate, ammonium thiocyanate, D(2)EHPA, TBP, Aliquat-336, tartaric acid, EDTA and organic solvents. Pre-concentration of lanthanum, yttrium and lutetium metal ions from dilute solutions was carried out.
Keywords: binary mixture; cellulose fiber membrane; Citric acid; complexing reagent; Lanthanum; lutetium; metal ions; Separation; transport studies; yttrium

Isobaric vapor-liquid equilibrium data for the binary systems of dimethyl carbonate with xylene isomers at 93.13 kPa - Yadav, S.S. (Journal of Chemical and Engineering Data, 2017)
Isobaric binary vapor-liquid equilibrium (VLE) data for dimethyl carbonate with xylene isomers (p-xylene, m-xylene, o-xylene, and ethylbenzene) were measured at the local atmospheric pressure of 93.13 kPa by using a dynamic recirculation still. The experimental VLE data were tested and found to be thermodynamically consistent by Herington and Van Ness consistency test. The experimental VLE data were correlated using the Wilson, NRTL, and UNIQUAC activity coefficient models and binary interactions parameters were estimated using a suitable objective function. The absolute mean deviation between the experimental and the model predicted values of vapor phase composition and total pressure was well within acceptable limits. No azeotrope was observed in any of the binary pairs and appeared to be easy for separation using conventional distillation method.
Keywords: Atmospheric Pressure; binary mixture; Distillation; Xylene

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect